2015
DOI: 10.1016/j.jep.2015.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological investigation of the diuretic and hemodynamic properties of native species of the Brazilian biodiversity

Abstract: The results presented here shown that the ES-EG obtained from E. grandiflorus leaves shown a significant diuretic and hypotensive activity and suggest that these effects could be related with an important renal and systemic vasodilator effect. In addition, it was shown for the first time that the pharmacological effects of ES obtained from P. tenellus and C. carthagenensis do not support its popular use as a diuretic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…Echinodorus grandiflorus is an important medicinal species known for its diuretic and antihypertensive effects [5, 6, 8]. Although some preclinical studies have shown the effectiveness of various preparations obtained from E. grandiflorus in different animal models, the effects on peripheral vascular resistance remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Echinodorus grandiflorus is an important medicinal species known for its diuretic and antihypertensive effects [5, 6, 8]. Although some preclinical studies have shown the effectiveness of various preparations obtained from E. grandiflorus in different animal models, the effects on peripheral vascular resistance remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical pharmacological studies have presented E. grandiflorus as a promising species for the treatment of cardiovascular diseases. Available data have shown that different preparations obtained from the species could present diuretic [5, 6], antiedematous [7], antihypertensive [68], and vasodilatory effects [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of different classes of secondary metabolites, including alkaloids, tannins, terpenoids, and saponins, has drawn attention [15,18]. However, polyphenolic compounds, including tannins, flavonoids, and C-glycosides, are worth mentioning because of their diuretic and antihypertensive effects [19,20]. Recent pharmacological studies have shown that different preparations that are obtained from E. grandiflorus have diuretic [19,20], antiedematous [18], anti-inflammatory [21,22], antihypertensive [20,23], and vasodilatory [24] effects, making the species a potential new candidate for herbal medicines.…”
Section: Heart-protective Effects Of Echinodorus Grandiflorus In Rabbmentioning
confidence: 99%
“…Os resultados foram expressos em porcentagem de área relativa de lesão.As plantas medicinais têm sido uma valiosa fonte de novas moléculas, sendo consideradas alternativas na busca de novos medicamentos(ZAKARIA et al, 2011). Há uma rica variedade de plantas medicinais que são utilizadas como gastroprotetoras naPrando et al (2015) detectaram a presença de vários taninos hidrolisáveis e flavonoides, tal como a quercetina, na fração aquosa das partes aéreas de P. tenellus. Os taninos hidrolisáveis foi observada em extrato aquoso e está em conformidade com Sprenger e Cass (2013).…”
unclassified